y=6/7-13

Simple and best practice solution for y=6/7-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y=6/7-13 equation:


y in (-oo:+oo)

y = 6/7-13 // - 6/7-13

y-(6/7)+13 = 0

y-6/7+13 = 0

y+85/7 = 0 // - 85/7

y = -85/7

y = -85/7

See similar equations:

| 30h+45=90 | | X^2-3x+2=4 | | 6x-11=25-2x | | 9v-11-5v=25 | | 17D/13 | | x:3/4=8 | | x^10=600 | | 8r-20=10 | | 2=3/7*x-13 | | (a+9)(a+1)= | | x+1/x+2=2 | | 5x+6=-66+7x | | x^2-800=0 | | 13m(3m-9)= | | 500=0.75*y | | p=160-8x-68x^2-2x^3+7x^4+x^5 | | -9(3h-8)= | | p(x)=0+(160)*x+(-8)*x^2+(-68)*x^3+(-2)*x^4+(7)*x^5+x^6 | | -16t^2+150= | | 3xsquare-4x-5=0 | | 4(5c+5)= | | 2.5-1.4n=3(0.2n+5) | | 28a+0.2=b | | -11x^2+3x+13=0 | | u/11=5 | | y=.25x-6.5 | | x^2+y^2+3xy+1=0 | | csquared=25 | | 2(4x+4)=20+4x | | 2(3-5p)=24-p | | x-5+2x-2=2x | | x=f*(1.8) |

Equations solver categories